Gross Domestic Regional Product, Population and Environmental Quality: Analysis of 33 Provinces in Indonesia - Ina Indriana; Nor Asmat Ismail; Siti Rahyla Rahmat (Journal of Applied Business, Taxation and Economics Research, 2021)
Abstract: In recent years environmental problems have become the focus of public attention in the world. The growth of the industry triggered by population growth is the main cause of the emergence of environmental problems. This research was conducted to determine the impact of Gross Domestic Regional Product growth, population growth on environmental quality. This study involved 33 provinces in Indonesia as a unit of analysis. Secondary data was collected from the Indonesian Central Bureau of Statistics. Data analysis was performed using panel least square with software Warp-PLS version 6.0. Previous research deployed CO2 Emission and pollution as an indicator of environmental performance, this research used a score of environmental quality index which covers water quality index, index of air quality and index of forest cover. Findings showed Gross Domestic Product and population have a negative effect on environmental quality. This research indicates government need to that encourages the household and industrial sectors to use environmentally friendly energy, limits and controls the conversion of forests and agricultural land into land for settlement, agriculture, and industry, and encourages the household and industrial sectors to provide waterways and ensure that liquid waste discharged into rivers, lakes or waterways does not harm the environment. Keywords : Gross Domestic Regional Product, Population, Environmental Quality